求证:化简[tan(A+B)-tanA-tanB]÷[tanA·tan(A+B)]=tanB.RT
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 10:18:55
求证:化简[tan(A+B)-tanA-tanB]÷[tanA·tan(A+B)]=tanB.RT
求证:化简[tan(A+B)-tanA-tanB]÷[tanA·tan(A+B)]=tanB.
RT
求证:化简[tan(A+B)-tanA-tanB]÷[tanA·tan(A+B)]=tanB.RT
tan(B)=tan(A+B-A)=(tan(A+B)-tanA)/(1+tanA*tan(A+B)
故:tanB/1=(tan(A+B)-tanA)/(1+tanA*tan(A+B)
由合比性质:
tanB/1=(tan(A+B)-tanA)/(1+tanA*tan(A+B)
=(tan(A+B)-tanA-tanB)/(1+tanA*tan(A+B)-1)
=[tan(A+B)-tanA-tanB]/[tanA·tan(A+B)]
证明:
[tan(A+B)-tanA-tanB]÷[tanA·tan(A+B)]
=[(tanA+tanB)/(1-tanAtanB) - (tanA+tanB)]/
[ tanA·(tanA+tanB)/(1-tanAtanB)]
=[(tanA+tanB)-(tanA+tanB)·1-tanAtanB] /
...
全部展开
证明:
[tan(A+B)-tanA-tanB]÷[tanA·tan(A+B)]
=[(tanA+tanB)/(1-tanAtanB) - (tanA+tanB)]/
[ tanA·(tanA+tanB)/(1-tanAtanB)]
=[(tanA+tanB)-(tanA+tanB)·1-tanAtanB] /
[tanA·(tanA+tanB)] 上下同时乘以1-tanAtanB 得
=[1-(1-tanAtanB)]/tanA 约去(tanA+tanB)
=tanB
收起